2017
DOI: 10.1007/978-3-319-51951-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Valuations and Curvature Measures on Complex Spaces

Abstract: We survey recent results in hermitian integral geometry, i.e. integral geometry on complex vector spaces and complex space forms. We study valuations and curvature measures on complex space forms and describe how the global and local kinematic formulas on such spaces were recently obtained. While the local and global kinematic formulas in the Euclidean case are formally identical, the local formulas in the hermitian case contain strictly more information than the global ones. Even if one is only interested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…; see ( 8) and (11) in the proof of Theorem 1. It should also be observed that the functionals φ r,s−2m,l+i n−1 can be expressed in terms of the functionals…”
Section: The Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…; see ( 8) and (11) in the proof of Theorem 1. It should also be observed that the functionals φ r,s−2m,l+i n−1 can be expressed in terms of the functionals…”
Section: The Main Resultsmentioning
confidence: 99%
“…Moreover, in the case k = n we use that φ r,s−2m,l+i n vanishes for m = s 2 . Hence, for even s we have to simplify the sum i Γ(i + l − 1) Γ( n 2 + l + i) × φ r,0, s 2 +l n (P, β)φ j (P ′ , β ′ ) = c s n,j φ r,0, s 2 +l n (P, β)φ j (P ′ , β ′ ), (11) as required. This completes the proof.…”
Section: This Givesmentioning
confidence: 99%
See 1 more Smart Citation